A patient-centred approach to deprescribing antiretroviral therapy in people living with HIV. (3rd August 2020) - Guaraldi, Giovanni; Milic, Jovana; Marcotullio, Simone; Mussini, Cristina
Abstract: Only a few studies have explored the benefit of deprescribing in people living with HIV (PLWH), focusing on the discontinuation of non-antiretrovirals (non-ARVs) used for HIV-associated comorbidities (co-medications), or the management of drug–drug interactions (DDIs) between ARVs or between ARVs and co-medications. The availability of modern single-tablet regimens, two-drug regimens and long-acting therapy opens a discussion regarding ARV deprescribing strategies. The objective of this article is to discuss ARV deprescribing strategies in the context of medication-related burden and patients' lived experience with medicine (PLEM) and to suggest indications for whom, when, how and why to consider these ARV options in PLWH. A PLEM construct helps to better interpret these strategies and provides a patient-centred precision-medicine approach. There are several safe and virologically effective ARV deprescribing strategies, but the ultimate benefits of these interventions still need to be further explored in terms of the overall health and quality of life of patients.